Interactions of Mitochondrial Presequence Peptides with the Mitochondrial Outer Membrane Preprotein Translocase TOM - Romero-Ruiz, Mercedes (The Biophysical Society, 2010)
TOM protein-conducting channels serve as the main entry sites into mitochondria for virtually all mitochondrial proteins. When incorporated into lipid bilayers, they form large, relatively nonspecific ion channels that are blocked by peptides derived from mitochondrial precursor proteins. Using single-channel electrical recordings, we analyzed the interactions of mitochondrial presequence peptides with single TOM pores. The largest conductance state of the translocon represents the likely protein-conducting conformation of the channel. The frequency (but not the duration) of the polypeptide-induced blockage is strongly modulated by the substrate concentration. Structural differences between substrates are reflected in characteristic blockage frequencies and duration of blockage. To our knowledge, this study provides first quantitative data regarding the kinetics of polypeptide interaction with the mitochondrial TOM machinery.